2015
DOI: 10.1182/blood-2015-01-622936
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 checkpoint blockade prevents immune dysfunction and leukemia development in a mouse model of chronic lymphocytic leukemia

Abstract: Key Points• In vivo PD-L1 blockade prevents CLL development in the Em-TCL1 adoptive transfer model. • In vivo PD-L1 blockade normalizes T-cell and myeloid cell populations and immune effector functions.Blockade of the programmed cell death 1 (PD-1)/programmed death-ligand 1 (PD-L1) immune checkpoint augments antitumor immunity and induces durable responses in patients with solid cancers, but data on clinical efficacy in leukemias are sparse. Chronic lymphocytic leukemia (CLL) is associated with a tumor-support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
154
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 40 publications
5
154
1
2
Order By: Relevance
“…61,63 Preclinical data on anti-PD-1 effects in CLL demonstrated restored CD8 T-cell cytotoxicity, immune synapse formation and prevention of CLL development in TCL-1 mouse models. 64,65 These observations and other preclinical data suggesting the importance of additional immune checkpoint pathways 66 provide a strong rationale for investigating immunomodulating therapies in CLL.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…61,63 Preclinical data on anti-PD-1 effects in CLL demonstrated restored CD8 T-cell cytotoxicity, immune synapse formation and prevention of CLL development in TCL-1 mouse models. 64,65 These observations and other preclinical data suggesting the importance of additional immune checkpoint pathways 66 provide a strong rationale for investigating immunomodulating therapies in CLL.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…These data indicate that PD-1 ligation delivers an inhibitory signal to CAR-mediated T-cell activation. Of interest, PD-L1 checkpoint blockade has been shown to normalize the T-cell compartment in the Em-TCL1 mouse model of CLL 30 ; however, even though PD-1 expression in CAR T cells in vivo has been observed, 8 its physiologic effects on the T-cell . Horizontal bars, boxes, and whiskers depict median, 25%/75% quartiles, and range, respectively.…”
Section: Prolonged Ibrutinib Treatment Decreases Immunosuppressive Pdmentioning
confidence: 99%
“…The Em-TCL1 model was selected because of its extensive prior characterization, including studies that demonstrated its utility in investigating tumor-induced immune defects. [50][51][52] Our results demonstrate that BRAF V600E accelerates Em-TCL1 B-cell leukemia development, likely because of a combination of decreased spontaneous apoptosis and enhanced immune suppression rather than increased proliferation. In addition, BRAF VE leukemia cells produced greater T-cell effects than Figure 6.…”
mentioning
confidence: 82%